Sustainability-oriented innovation system and economic stability of the innovative countries - Faiza Manzoor; Longbao Wei; Qazi Abdul Subhan; Mahwish Siraj (Frontiers Media S.A., 2023)
Novelcoronavirus-19 has created a challenging situation for developed as well as developing countries to sustain economic stability. There are a lot of controversies for policymakers to formulate an effective policy for reviving economic stability and minimizing the economic effects of this pandemic. The present study focuses on the internal mechanism of the Sustainability Oriented Innovation System and its subsequent effects on economic stability in most innovative economies. For empirical analysis of the most innovative countries (12 countries) high-income, middle-income, low-income, and lower-middle-income countries are selected. The Sustainability Oriented Innovation System is represented through the innovation input index and innovation output index. Economic stability is measured through the GDP growth rate of respective countries. A set of panel data was developed for the period of 11 years and Fixed Effect Methods were used to ascertain the empirical findings. The outcomes indicate that innovation is the main force of economic stability. The study's results are important to policymakers to promote, stimulate and support economic stability through their strategies. Future studies may focus on the effects of the Sustainability Oriented Innovation System on economic stability in regional blocks like the EU, ASEAN, and G-20 countries.